The Development of Hierarchy of Effects Model in Advertising - Wijaya, Bambang Sukma (Universitas Prasetiya Mulya, 2012)
This paper aims to review the hierarchy of effects models in advertising, especially the well-known model, AIDA (Attention, Interest, Desire, and Action). Since its introduction by Lewis (1900) and generally attributed in the marketing and advertising literature by Strong (1925), the concept of AIDA’s hierarchy of effects model has been used by many researchers, both academicians and practitioners. The model is used to measure the effect of an advertisement. However, the development of information technology has radically changed the way of how people communicate and socialize; as well as a paradigm shift from product-oriented marketing to consumer-oriented marketing or people-oriented marketing. Therefore, the variables in the hierarchy of effects model needs to be updated in respond to the latest developments in the notice of public power as consumer audience. Based on deep literature review and reflective method, this paper introduces a new developed concept of hierarchy of effects model that was adopted from AIDA’s hierarchy of effects model, namely: AISDALSLove (Attention, Interest, Search, Desire, Action, Like/dislike, Share, and Love/hate).